CT Texture Analysis for Differentiating Bronchiolar Adenoma, Adenocarcinoma In Situ, and Minimally Invasive Adenocarcinoma of the Lung - Sun, Jinju; Liu, Kaijun; Tong, Haipeng; Liu, Huan; Li, Xiaoguang; Luo, Yi; Li, Yang; Yao, Yun; Jin, Rongbing; Fang, Jingqin; Chen, Xiao (Frontiers in Oncology, 2021)
Purpose: To investigate the potential of computed tomography (CT) imaging features and texture analysis to distinguish bronchiolar adenoma (BA) from adenocarcinoma in situ (AIS)/minimally invasive adenocarcinoma (MIA). Materials and Methods: Fifteen patients with BA, 38 patients with AIS, and 36 patients with MIA were included in this study. Clinical data and CT imaging features of the three lesions were evaluated. Texture features were extracted from the thin-section, unenhanced CT images using AnalysisKit software. Then, multivariate logistic regression analysis based on selected texture features was employed to distinguish BA from AIS/MIA. Receiver operating characteristics curves were performed to determine the diagnostic performance of the features. Results: By comparison with AIS/MIA, significantly different CT imaging features of BA included nodule type, tumor size, and pseudo-cavitation sign. Among them, pseudo-cavitation sign had moderate diagnostic value for distinguishing BA and AIS/MIA (AUC: 0.741, 0.708, respectively). Further, a total of 396 quantitative texture features were extracted. After comparation, the top 6 texture features of the most significant difference between BA and AIS or MIA were chosen. The ROC results showed that these key texture features had high diagnostic value for differentiating BA and AIS or MIA, among which the value of a comprehensive model with selected 6 texture features was the highest (AUC: 0.977, 0.976, respectively) for BA and AIS or MIA. These results indicated that texture analyses can effectively improve the efficacy of thin-section unenhanced CT for discriminating BA from AIS/MIA. Conclusion: CT texture analysis can effectively improve the efficacy of thin-section, unenhanced CT for discriminating BA from AIS/MIA, which has potential clinical value and helps the pathologist and clinicians to make diagnostic and therapeutic strategies.